Development of Biodiversity Booklet in Demak Regency as a Supplement of Teaching Material - Nur Cahya Anggita Maharani; Nur Kusuma Dewi (Universitas Negeri Semarang, 2024)
Biology is a subject that is closely related to living things and their environment. Biology learning especially on biodiversity material, must be relevant to the lives of students, therefore it is needed to develop teaching materials based on the local potential to maximize learning processes and learning outcomes. This research aims to analyze biodiversity in Demak Regency, analyze feasibility and readability, and measure the increase of student learning outcomes when using biodiversity booklet in Demak Regency as a supplement of teaching material. This research was conducted at SMA Negeri 3 Demak in the odd semester of 2022/2023. The research uses Research and Development (RnD) type. To analyze the increase in cognitive learning outcomes using the One-Group-Pretest-Posttest-Design, to analyze psychomotor and affective learning outcomes using the One-Shot Case Study. The subjects to collect readability data are 15 students of class X-10 taken by purposive sampling technique and the subjects to collect learning outcomes data are students of class X-8. The results showed that gene-level diversity was found in water apple or Syzygium aqueum (Burm. f.) Alston and starfruit or Averrhoa carambola L. varieties, species diversity of mangrove that was found are 20 mangrove species, and have been found 9 types of ecosystem-level diversity. Booklet validity based on material expert’s judgment was 83,33%, 85,42% from media experts, and 88,88% from biology teacher, with